2023
DOI: 10.3390/gels9020081
|View full text |Cite
|
Sign up to set email alerts
|

Visualized Study on a New Preformed Particle Gels (PPG) + Polymer System to Enhance Oil Recovery by Oil Saturation Monitoring Online Flooding Experiment

Abstract: After tertiary recovery from the oilfields, improving the production of the remaining hydrocarbon is always challenging. To significantly improve oil recovery, a heterogeneous composite flooding system has been developed with preformed particle gels (PPG) and polymers according to the technical approach of plugging and flooding combination. In addition, an oil saturation monitoring device and a large-scale 3D physical model were designed to better evaluate the performance of the technique. The evaluation resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…(2) Saturating of the core samples with the crude oil sample was conducted, and irreducible water saturation was obtained. The specific process can be seen in [ 37 , 38 ]. After that, the condition was maintained for 12 h.…”
Section: Methodsmentioning
confidence: 99%
“…(2) Saturating of the core samples with the crude oil sample was conducted, and irreducible water saturation was obtained. The specific process can be seen in [ 37 , 38 ]. After that, the condition was maintained for 12 h.…”
Section: Methodsmentioning
confidence: 99%
“…[13]. Among the in-depth fluid diversion agents, precrosslinked particle gel (PPG) has garnered attention [14], with researchers utilizing its plugging effect to block high-flow channels and expand the volume of displacement fluids. Wang designed a heterogeneous composite system for the post-polymer flood reservoir in Shuanghe Oilfield and conducted experiments, including flooding agent optimization [15], thermal stability evaluation, and injection method optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Alkali: Anhydrous Na 2 CO 3 with a purity of 99%. According to the data obtained from the core samples retrieved from a typical block in Daqing Oilfield [14], the permeability of the high, medium, and low reservoir layers was approximately 4000, 2000, and 500 (×10 −3 µm 2 ), respectively. The ratio of reservoir thickness was approximately 18:45:20.…”
mentioning
confidence: 99%
“…Polymer flooding technology has become an important means of enhancing oil recovery in China's high water-cut oilfields and has been applied in large-scale industrial applications in the Shengli and Daqing oilfields [5,6]. Studies have shown that polymer flooding can effectively expand the swept volume and improve displacement efficiency.…”
Section: Introductionmentioning
confidence: 99%